Bordering nowhere: migration and the politics of placelessness in contemporary art of the Maghrebi diaspora. Issue 2 (14th March 2016) - Demerdash, Nancy N. A.
ABSTRACT: Inasmuch as the events of 2010 and 2011 ushered in tremendous shifts in political consciousness across the Mashreq and Maghreb, they too increased the mass movements and migrations of humanity. That Maghrebi spheres of cultural production have sought to document and problematise these seismic transformations is undeniable. While narratives of hardship, stagnation, and political struggles undergird most analyses of the post-revolutionary Maghreb and discourses of migration, this essay seeks instead to demonstrate how the visual strategies of contemporary artists render the traumas of dislocation – both real and metaphysical – and in turn, engender a politics and aesthetics of placelessness. This essay probes into the placeless nature of not only the artists' liminal operations but also explores the conceptual methods through which the tensions of migrancy are manifest. Yet, the question remains: How does the trope of the border inform the creative expressions of not only entrapment, but endless mobility? In what ways do these artists adopt visual praxes that are politically engaged? How do fraught and layered transnational narratives of migration speak to the complexities of placelessness and displacement? How are the figure and position of the migrant visually treated in their works? Commanding a transregional and liminal visuality, and guided by the works of artists such as Bouchra Khalili, Yto Barrada, Kader Attia, Driss Ouadahi, Mohamed Ben Slama, Zineb Sedira, and Moufida Fedhila, among others, this essay theorises the political junctures and paradoxes of place/placelessness, and the transnational networks of empathy and solidarity in which these artists' works are inscribed.